BIBLIOMETRIC ANALYSIS OF THE ROLE OF THE MILITARY IN NATIONAL DEVELOPMENT USING VOSVIEWER APPLICATION - Brantas Suharyo G; Marsetio Marsetio; I Wayan Midhio; Anwar Kurniadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Bibliometric Analysis is a means of mapping the latest research using meta data processing using Google Scoler. This study aims to determine the latest research developments on the role of the military. Step-by-step analysis is provided to make it easier for first-time users to access and utilize VOSViewers. This provides data analysis on the role of the military so far by utilizing the mapping tool in VOSViewer. The method used is descriptive qualitative to describe the bibliometric performance of the analysis by producing a visualization of the selected topic network. From the search results, 104 relevant journals published from 2006 to 2023 were found, which were then grouped into five categories according to their year of publication. After grouping the journal data, we found that the total number of articles published linked to the topic of the role of the military was 27 articles. As a result, it is concluded that the military is a field that can be combined with other fields to be studied. This is a way to show many opportunities to find new things to determine the theme. Furthermore, this analysis is expected to function as a source for researchers to conduct research and determine research themes.